Antígenos circulantes no diagnóstico da Esquistossomose mansoni em residentes de área de alta endemicidade no Nordeste do Brasil - Bezerra, Danielle de Freitas (2020)
Schistosomiasis is a neglected tropical disease that affects about 230 million people worldwide and in Brazil it is estimated that about 25 million people live in regions at risk for a disease. The state of Sergipe has one of the highest prevalences in the country, where schistosomiasis is endemic in 51 of the 75 municipalities. The last intervention carried out in the locality of Siebra was in 2008, and showed a prevalence of 37.9%, according to data from SES-SE. The detection of circulating antigens from Schistosoma mansoni has become an alternative diagnostic tool in active infections. The levels of these antigens are believed to be related to the parasitic burden and the intensity of the infection. The objective of the study was to evaluate the performance of the POC-CCA in a highly endemic area in Northeast Brazil, comparing the Kat-Katz and ELISA techniques, in addition to verifying the correlation between the measurements of the test's immunochromatographic reaction, with parasitic load in OPG. The prevalence, sensitivity, specificity, Positive Predictive Value (VPP), Negative Predictive Value (VPN), Accuracy, Kappa Coefficient and Spearman correlation were calculated using the Kato-Katz technique and POC-CCA test. 95% confidence. For comparative analyzes, 06 Kato-Katz slides were used as a reference standard. In some conflicting results between tests tested, a urine filtering step without a POC-CCA test was used in an attempt to improve its accuracy. The correlation between the intensity of the reaction in the POC-CCA and the number of eggs per gram of feces (OPG) was evaluated, calculated using the Kato-Katz technique. The prevalence of schistosomiasis with the ELISA technique was 58.86%, while Kato-Katz was 48.82%, and the rates of positivity by POC-CCA were positive (t +) and negative (t-). 66.14% and 45.24%, respectively. The POC-CCA (t +) test showed sensitivity of 88.31%, specificity of 51.85%, positive predictive value (PPV) of 63.55% and negative predictive value (NPV) of 82.35%, with accuracy 69.62%, considering the Kato-Katz method as the reference standard, and the agreement with the Kappa index and the agreement between both tests was weak. The POC-CCA (t-) test showed sensitivity of 76.62%, specificity of 83.65%, PPV of 81.94%, VPN of 79.07%, and precision of 80.38%, considering the Kato method -Katz, as a reference, and according to the Kappa index, agreement between both tests was moderate. Analyzing a correlation between parasitic load (in OPG) with a semi-quantification of the intensity of the immunochromatographic reaction, we found that the agreement between the results was 55%, with the Kappa index of 0.30, being considered as weak, as a correlation of Spearman (r = 0.54) was considered moderate. The POC-CCA showed a good performance in the diagnosis with medium and high EPG, presenting a reasonable correlation between a semi-quantitative POC-CCA scale and the EPG, individually, but with a high number of false physical effects in the phases. CCA-FLT improves diagnostic accuracy over conventional POC-CCA. The ELISA showed 100% agreement on high and moderate EPG, but only 82.3% sensitivity at low parasitic load.